Brute Force Algorithm Implementation Of Dictionary Search - Charles Baturu; Naufal abdi (Jurnal Info Sains : Informatika dan Sains, 2020)
In the manual dictionary the more words are accommodated, the heavier the dictionary. Dictionaries that are generally book-shaped are difficult to carry anywhere because they are thick and heavy. With this mobile-based computer dictionary application, users no longer need to carry heavy dictionaries and the search process will also be faster and easier. This mobile-based kmputer dictionary application is created using the java programming language with the NetBeans 7.0 editor and using an RMS (Record Management System) based database. So it can be installed on various types of mobile phones that already support Java. String Matching is one of the algorithms used to speed up the search process for the desired word. String matching algorithms have been used frequently before as examples in the process of matching strings based on the equation of text data namely Brute Force. Because this Brute Force algorithm can be used to perform string or text searches. Brute force algorithm is an algorithm to match a pattern with all text between 0 and n-m to find the presence of a pattern in text.